The first evaluation of glucose-6-phospate dehydrogenase defciency (G6PD) gene mutation in malaria endemic region at South Central Timor (SCT) district, Eastern Indonesia 2014–2015 - Jontari Hutagalung; Hari Kusnanto; S. Supargiyono; P. Purwono; Sadewa Ahmad Hamim; Darojatun Ida; Satyagraha Ari Winasti; Novijanti Rintis; Triwibowo A. Garjito; Mega Tyas Prihatin; Bai Apris; Bansai Immanuel; Kik Hao Samuel; Hananta Linawati (Universitas Gadjah Mada, 2015)
Primaquine (PQ) is a key drug in the malaria pre-elimination stage. However, PQ can trigger acutehemolysis for people with G6PD defciency (G6PDd). In 2013, 15–25 million Indonesian people were infected with malaria, with 30,000–38,000 deaths each year mostly in eastern Indonesia with API= 15.6 %. Recently, the Ministry of Health of the Republic of Indonesia announced a plan to reach the pre-elimination stage based on WHO guidelines. This study assesses whether eastern Indonesia should proceed with the activities of malaria pre-elimination. A total 555 healthy people in fve subdistricts in eastern Indonesia were selected by systematic random samping. All data were collected using a standard questionnaire, physical examination, and laboratory tests. PCR and DNA sequencing protocols followed respective manufacture’s instructions. Statistical analysis by bivariate with α= 0.05 and 95% CI were performed using the SPSS software package. Based on the nested PCR, the result showed a malaria prevalence of 32.6% with being the dominant species (52.5%). Malaria cases were found in all study sites and not using a bed net was the moost signifcant risk factors with Exp B= 1.54 with 95% CI= 0.99–2.38. G6PDd prevalence was 16.6%, the highest G6PDd ever found in Indonesia with variant molecular dominant 10.883 T>C and one sample with a heterozygous female. Malaria pre-elimination in eastern Indonesia should be delayed. High risk patients should be tested for enzyme G6PD activities before antimalarial administration.